Highly reflective metallic thin films for high brightness LEDs - Bay, Yang Jie (2017)
The development of LEDs towards better performance has always been an essential part of research in this field, and maximal reflectance is the key to achieving high performance LEDs. Amongst the components that make up an LED, the silver-plated lead frame is the main component that contributes to the amount of light emission of LEDs. By investigating the factors that can affect the reflectance of the silver on the lead frame, one can then manipulate these properties of the plated silver in order to obtain high reflectance. Silver samples obtained from two different plating baths were investigated. One obtained from a solution with cyanide addition and the other produced by cyanide-free solution. A comparison in reflectivity between the two types of silver was done to justify the advantages of cyanide and also to gather information on whether cyanide-free silver could potentially be used as a replacement for cyanide-based plated silver. It was found that reflectivity of the plated silver can be influenced by several factors such as surface morphology, preferred crystal plane of orientation for achieving highest reflectivity and lastly surface roughness. There was great contrast in terms of surface morphology between the captured SEM images of the cyanide-free and low-cyanide images with cyanide-free plated silver displaying more surface irregularities than the silver obtained from low-cyanide bath. Reflectance results showed that low-cyanide silver had better optical properties than the cyanide-free silver, before and after heat treatment. The reflectivity only varied by a small margin after the heat treatment, thus reflectivity is unaffected by increased temperatures. SEM images captured showed higher amount of surface irregularities in the cyanide-free silver. XRD results reflected broader peak widths of the cyanide-free silver, indicating smaller crystallite sizes than the low-cyanide silver. (111) plane lattice was also determined to be the preferred orientation for maximum reflectance to be obtained even after heat treatment. AFM roughness values were obtained from both cyanide-free and low-cyanide samples. The roughness values of the individual samples were correlated against the reflectance values to form a relationship between surface roughness and reflectance. The results of each analysis were obtained and used to form relationships against the reflectance. By establishing the effect that these properties have on reflectance, one can then determine how to manipulate these properties to achieve maximum reflectivity.